2006
DOI: 10.1021/jp058244z
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ Al K-Edge XAS Investigation of the Local Environment of H+- and Cu+-Exchanged USY and ZSM-5 Zeolites

Abstract: Aluminum coordination in the framework of USY and ZSM-5 zeolites containing charge-compensating cations (NH4+, H+, or Cu+) was investigated by Al K-edge EXAFS and XANES. This work was performed using a newly developed in-situ cell designed especially for acquiring soft X-ray absorption data. Both tetrahedrally and octahedrally coordinated Al were observed for hydrated H-USY and H-ZSM-5, in good agreement with 27Al NMR analyses. Upon dehydration, water desorbed from the zeolite, and octahedrally coordinated Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 78 publications
11
61
0
Order By: Relevance
“…After deconvolution, the average spectra of the masked zeolite regions within the fresh FCC catalyst particle closely resemble that of am easured reference zeolite Ys pectrum (Figure 2b,F igures S6-9). [33] It was found that the aging trends,a sd etermined by the increasing metals content in each FCC catalyst particle, correspond very well with ad ecrease in the amount of tetrahedrally coordinated Al (Figure 2b). [8,32] Subsequently,anon-negative linear combination least-squares fit was performed with three reference compounds:t hat is,p ure 4-coordinated Al (ZSM-5), a-alumina (6-coordinated Al, oxide), and boehmite (6-coordinated Al, oxyhydroxide).…”
mentioning
confidence: 61%
“…After deconvolution, the average spectra of the masked zeolite regions within the fresh FCC catalyst particle closely resemble that of am easured reference zeolite Ys pectrum (Figure 2b,F igures S6-9). [33] It was found that the aging trends,a sd etermined by the increasing metals content in each FCC catalyst particle, correspond very well with ad ecrease in the amount of tetrahedrally coordinated Al (Figure 2b). [8,32] Subsequently,anon-negative linear combination least-squares fit was performed with three reference compounds:t hat is,p ure 4-coordinated Al (ZSM-5), a-alumina (6-coordinated Al, oxide), and boehmite (6-coordinated Al, oxyhydroxide).…”
mentioning
confidence: 61%
“…To follow the effect of Al-Cu scattering distance, a systematic variation from 2.71 to 2.89 Å was made, as done in previous work. 23 2.4. Mass Spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of occluded CuCl has also been observed by Cl K-edge XANES in Cu-USY prepared in a manner similar to that used in this study. 23 Preparation of the Cu-Y by vapor-phase exchange of H-Y with CuCl required handling of H-Y in the absence of water vapor. Moreover, once exposed to water vapor, hydrated H-Y cannot be dehydrated without a loss in the crystallinity of the zeolite.…”
Section: Preparation and Site Occupancy Of Cu-ymentioning
confidence: 99%
“…Details of this procedure have been described elsewhere [8][9][10][11]. Freshly prepared catalysts, designated as Cu-Y, Cu-ZSM-5, and Cu-MOR, were stored in a drybox before use.…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%